Does the discontinuation time of antiplatelet or anticoagulation treatment affect hemorrhagic complications in patients undergoing craniotomy for neurovascular lesions?. (3rd September 2021) - Ebel, Florian; Ullmann, Muriel; Guzman, Raphael; Soleman, Jehuda
Abstract: Background: The number of patients treated with platelet inhibitors (PI) and/or anticoagulants (AC) in neurosurgery is increasing. The aim of this study was to analyse the effect of PI/AC discontinuation time on hemorrhagic events after craniotomy for neurovascular pathologies. Methods: The 30-day postoperative bleeding rates were retrospectively compared between short (≤5 days) and long (>5 days) discontinuation time of PI/AC before and after surgery. Kaplan-Meier survival analysis comparing time to postoperative bleeding and the effect of PI/AC discontinuation time on bleeding rates were analysed. Potential risk factors for postoperative bleeding were further analysed in uni- and multivariate analysis. Results: Out of 215 consecutive patients undergoing craniotomy for neurovascular lesions between January 2009 and April 2019, 23.3% were treated with PI/AC. Of these 36% ( n = 18) and 20.8% ( n = 10) were included in the short pre- and postoperative discontinuation group, respectively. Bleeding rates were comparable between the pre- and postoperative short and long discontinuation groups (preoperative 11.1% vs 10%, p = .659; postoperative 0% vs 13.2%, p = .566). In-hospital mortality rates and time to bleed of the groups were comparable as well. Similarly, the rate for thromboembolic events was not significantly affected by the pre- or postoperative discontinuation time of PI/AC. After multivariate analysis preoperative bleeding of the lesion was significantly associated with postoperative bleeding. Conclusions: Patients with short discontinuation time of PI/AC treatment undergoing craniotomy for the treatment of neurovascular lesions do not appear to have increased rates of postoperative bleeding.